Can social spending cushion the inequality effect of globalization? - Andreas Bergh; Irina Mirkina; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2019)
This paper examines whether social spending cushions the effect of globalization on within-country inequality. Using information on disposable and market income inequality and data on overall social spending, and health and education spending from the ILO and the World Bank/WHO, we analyze whether social spending moderates the association between economic globalization and inequality. The results confirm that economic globalization - especially economic flows - associates with higher income inequality, an effect driven by non-OECD countries. Health spending is strongly associated with lower inequality, but we find no robust evidence that any kind of social spending negatively moderates the association between economic globalization and inequality.
Keywords: I10; 330; Globalization; Social spending; Income inequality